2020
DOI: 10.1002/psp4.12540
|View full text |Cite
|
Sign up to set email alerts
|

Mini‐Review: Comprehensive Drug Disposition Knowledge Generated in the Modern Human Radiolabeled ADME Study

Abstract: The human radiolabeled absorption, distribution, metabolism, and excretion (ADME) study offers a quantitative and comprehensive overall picture of the disposition of a drug, including excretion pattern and metabolite profiles in circulation and excreta. The data gathered from the ADME study are highly informative for developing a cohesive strategy for clinical pharmacology studies. Elements of standard ADME study designs are described. An exciting new development in human ADME studies is the application of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…MB studies traditionally use the clinically intended route of administration. While sufficient to address MIST objectives, the value of information from this study can be greatly enhanced for PBPK model development if evaluation of absolute bioavailability is built in 4 . If feces are analyzed for parent drug following intravenous (IV) administration, quantification of biliary plus intestinal secretory clearance will be possible.…”
Section: The Pivotal Role Of the Human Mb Studymentioning
confidence: 99%
“…MB studies traditionally use the clinically intended route of administration. While sufficient to address MIST objectives, the value of information from this study can be greatly enhanced for PBPK model development if evaluation of absolute bioavailability is built in 4 . If feces are analyzed for parent drug following intravenous (IV) administration, quantification of biliary plus intestinal secretory clearance will be possible.…”
Section: The Pivotal Role Of the Human Mb Studymentioning
confidence: 99%
“…Mass balance studies are performed to identify and quantify metabolites and determine characteristics of the elimination pathways. [10][11][12] An increasingly popular approach for determining absolute bioavailability is use of a microtracer dose. [13][14][15][16][17] In the phase 1 human mass balance study reported herein, belumosudil PK was characterized in humans after oral doses of 200 mg (unlabeled belumosudil tablet and [ 14 C]-belumosudil capsule) and a radiolabeled intravenous (IV) microtracer.…”
mentioning
confidence: 99%
“…Indeed, for the integrated approach only very low amounts of radiolabeled compound are needed, so that no determination of radiation burden is required, and hence, no quantitative whole-body autoradiography in rodents is to be conducted. In addition, the very low amounts used do not require to be produced according to Good Manufacturing Practice ( Ufer et al, 2017 ; Spracklin et al, 2020 ). However, for such an integrative approach a highly sensitive technique is needed, which is realized by the application of AMS ( Graham and Garner, 2003 ; Lappin et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it provides key information on relevant drug interactions or dosing of special patient populations such as renally or hepatically impaired patients. Given the importance of understanding those characteristics, human ADME studies should be conducted during early clinical development ( Spracklin et al, 2020 ). This can be achieved, for example, with a human microtracer component incorporated into a first-in human (FIH) study.…”
Section: Introductionmentioning
confidence: 99%